Long-term survival in out-of-hospital cardiac arrest patients treated with targeted temperature control at 33 °C or 36 °C: A national registry study. (October 2019) - Abazi, Lis; Awad, Akil; Nordberg, Per; Jonsson, Martin; Taccone, Fabio S.; Wickerts, Carl Johan; Svensson, Leif; Hollenberg, Jacob; Ringh, Mattias; Forsberg, Sune
Abstract: Aim: There are limited data on long-term outcome in out-of-hospital cardiac arrest patients following the treatment shift of target temperature management (TTM) from 33 °C to 36 °C outside the controlled settings of randomised trials. The aim of this study was to evaluate the adherence to TTM guidelines after the publication of the TTM trial and if the change in temperature level influence six-month survival. Methods: OHCA patients admitted to intensive care units (ICU) and recorded in the Swedish Intensive Care Registry (January 2010–March 2016) were included. Each ICU in Sweden provided information on their TTM target (i.e. 33 °C [TTM33] or 36 °C [TTM36]) used and the date of shift to 36 °C. The primary outcome was six-months survival. Multivariate logistic regression and propensity score match was used to adjust for confounders. Results: In total, 2899 OHCA patients from 69 ICUs were assessed; of those, 1038 patients were treated with TTM (TTM33, n = 755 and TTM36, n = 283). Patients receiving any TTM decreased during the study period from 70.5% to 54.5% (p for trend <0.001). There was no significant difference in six-month survival between the TTM33 (47.2%) and the TTM36 (47.3%) groups (adjusted OR 1.12 [0.80–1.56]. In the propensity score matched analysis the six-months survival was 52.7 vs 47.3 %, OR 1.29 [0.90–1.85]). Conclusions: The proportion of patients receiving therapeutic hypothermia in Sweden has decreased significantly since the publication of the TTM-trial indicating lower adherence to guidelines. This was not associated with any significant difference in long term outcome.